ANALISIS KETERAMPILAN MEMBACA PERMULAAN PADA SISWA KELAS III DI SDN 1 GUNUNGSARI - Celline Reyhasie Freancis; Lina Erviana; Wulan Trisnawaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Beginning reading skills are basic abilities that elementary school students must master to build a foundation for understanding learning materials. This study aims to describe the initial reading skills of third-grade students at SDN 1 Gunungsari, identify the factors that influence them, and explain the strategies teachers use to develop these skills. The study employs a qualitative approach with descriptive methods and a case study design. The research subjects include a third-grade teacher and 15 students. Data were obtained through observation, interviews, tests, questionnaires, and documentation and then analyzed using the Miles and Huberman model with source and technique triangulation. The results of the study indicate that 13 students have good initial reading skills, while 2 students still experience difficulties in phonetic aspects, reading fluency, and reading comprehension. Reading ability is influenced by both internal and external factors. The teacher implements loud reading exercises, group reading, and the use of letter cards and word cards, as well as learning assistance according to student needs, to enhance initial reading skills in a continuous, effective, and comprehensive manner for all students.